Myanmar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes how Myanmar can manage its natural resources for people's development. Myanmar's natural resource endowments provide much needed national wealth to finance the country's development. Given Myanmar's low tax revenue, mobilizing resource revenues is particularly important in the current macroeconomic environment of widening fiscal and current account deficits, inflationary pressures and exchange rate depreciation. The government should consider revising the fiscal regime for natural resources and introducing a resource rent tax to maximize the revenue stream in an efficient way. To better manage the impact of volatile resource revenues on the budget, consideration could be given to anchoring fiscal policy on an expenditure rule over the medium term.